Association of plasma BMP6 levels with the rates of brain atrophy in older people without dementia - Zhang, Xin; Fu, Pan; Cai, Yan (Frontiers in Neurology, 2025)
BackgroundBone morphogenetic protein 6 (BMP6) has been implicated in the pathogenesis of Alzheimer's disease (AD), and its levels have been reported to be associated with cognitive performance. However, few studies have examined the association between plasma BMP6 levels and brain atrophy in older adults.MethodsA total of 340 older adults without dementia were included in the current study. Study participants had baseline plasma BMP6 data available and at least two structural MRI scans. Volumes of six brain regions were measured, including the hippocampus, entorhinal cortex, middle temporal gyrus, fusiform gyrus, ventricles, and whole brain. A series of linear mixed-effects models were built to examine the associations of plasma BMP6 levels with brain atrophy over time.ResultsOur study revealed that higher plasma BMP6 levels were associated with a reduced rate of volume loss in the hippocampus, entorhinal cortex, middle temporal gyrus, and whole brain. However, there was no significant link between plasma BMP6 levels and changes in the volume of the fusiform gyrus or ventricles.ConclusionOur results may provide novel insights into the mechanisms of neurodegeneration in AD, contributing to new avenues for timely intervention and potentially slowing disease progression.